MEDIUM AS THE MESSAGE: PROVERB AS A MEDIUM OF COMMUNICATION IN EPHRAIM EZE OKWOR’S A RIDDLE FOR THE GODS - ANASI, Obumneme Francis (EBSU Journal of Social Sciences and Humanities, 2024)
Marshal Mcluhan, the Canadian Communicator in the 1960s, says in his book The Medium is the Message, that no single message is as important as the medium through which it is conveyed. Understanding a message is dependent on the manner, the approach, the how that the message is disseminated. By this ,the medium is the sine qua non of any communication. Based on the above principle, this work will examine the proverbs extracted from Ephraim Okwor’s A Riddle for the Gods as medium of communication. So this work will do an objective examination of the proverbs in use. African folklore, according to Asika (2009), has become part and parcel of what literary African artists weave in their works in order to give it a true touch of beauty and glamour; something African and very close to their hearts. Building on the above premise, this work will analyse the proverb as a means of communication. Proverb in this instance is not just the metaphorical oil with which the Igbos eat words but the literally palm-oil with which good, genuine, believable African stories are told and in respectable manner. The work studies proverbs as a medium of communication. Since medium is the message, this work examines how the author of A Riddle for the Gods, was able to present his proverbs to be able to communicate effectively and accordingly.